ZnO-Porous Clay Heterostructure from Saponite as Green Catalyst for Citronellal Cyclization - Dwiarso Rubiyanto; Nurcahyo Iman Prakoso; Imam Sahroni; Rico Nurillahi; Is Fatimah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Green conversion in organic synthesis is one of the interesting and important topics in green chemistry. The use of heterogeneous catalysis instead of homogeneous catalysis offers some advantages, such as easy separation and reusability. In this research, a heterogeneous acid catalyst was prepared from saponite by immobilizing ZnO in the form of a pillared clay (Zn/PILS) and Zn supported on porous clay heterostructure (Zn/PCH). Physicochemical studies involving X-ray diffraction measurement, surface analysis using a gas sorption analyzer, and surface acidity measurement were performed. Results indicated that the increasing surface acidity and the high specific surface area of the material were the relevant physicochemical properties that facilitate environment-friendly citronellal cyclization. The higher values for both parameters in Zn/PCH than in Zn/PILS linearly affected citronellal conversion and the selectivity for isopulegol production. Zn/PCH demonstrated a conversion rate of 98.9% for a 3-hour reaction and a selectivity of 100% for isopulegol production, and it exhibited reusability properties. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).